2020
DOI: 10.1186/s12905-020-00913-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of switching from minodronate to denosumab treatment in patients with postmenopausal osteoporosis: a retrospective study

Abstract: Background: Denosumab is a major treatment option for patients with postmenopausal osteoporosis; however, the evidence for its use is lacking. Therefore, in this 24-month retrospective study, we aimed to evaluate the effects of switching from minodronate (MIN) to denosumab in these patients. Methods: Patients with postmenopausal osteoporosis either switched from MIN to denosumab (Group 1; n = 32) or continued MIN treatment (Group 2; n = 24). Bone mineral density (BMD) of the lumbar spine (L2-L4) and femoral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the present study, the serum calcium levels did not change significantly in either group, and this is consistent with the findings of previous studies ( Nakamura et al, 2017 ; Kobayashi et al, 2020 ). However, we previously reported that a high bone turnover elevates the risk of denosumab-induced hypocalcemia ( Ishikawa et al, 2018a ; Ishikawa et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the serum calcium levels did not change significantly in either group, and this is consistent with the findings of previous studies ( Nakamura et al, 2017 ; Kobayashi et al, 2020 ). However, we previously reported that a high bone turnover elevates the risk of denosumab-induced hypocalcemia ( Ishikawa et al, 2018a ; Ishikawa et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
“…In another study of patients who had used oral bisphosphonate treatment before, it was reported that denosumab achieved more significant results in total vertebrae, total hip and radius BMD scores compared to zolendronic acid (19). In another study, conducted with minodronate, which is a third generation bisphosphonate and known as the strongest bisphosphonate, more significant improvements were found in BMD and bone turnover markers in the group that switched from minodronate to denosumab treatment compared to the group that continued to use minodronate (20). In a meta-analysis of 5361 patients by Lyu et al, in which denosumab and bisphosphonates were compared, it was concluded that denosumab increased the total hip, femoral neck, and total lumbar vertebrae BMD scores more (21).…”
Section: Discussionmentioning
confidence: 98%
“…In several studies, BMD increased when switching from oral bisphosphonate to denosumab in clinical practice; however, most studies only investigated BMD in the short term or for approximately 1 year [ [25] , [26] , [27] , [28] ]. Indeed, studies conducted over a longer period (2 years or more) are scarce [ 29 , 30 ]. The increase in BMD after switching from bisphosphonate treatment to denosumab may account for the different mechanisms of action of the 2 drugs.…”
Section: Discussionmentioning
confidence: 99%